Supply Chain Management Issues for E-Commerce Companies Offering Quality Guarantee To the Market - Du, Xiaoxin (2011)
Under the economic globalization and the information technology revolution, e-commerce has become an effective solution for firms which are facing intensive domestic competition, pursuing further development, seeking better market communication, and exploring opportunities of minimizing supply chain management cost. However, with the continuous development of e-commerce, management issues are also exposed. Product and service quality problem has been seen as the biggest challenge of e-transaction for years (Sina.com, 2011). Managing e-commerce companies’ product and service quality system to achieve customer satisfaction involves: designing goods with right performance to meet customer demands, providing proper quality guarantee, and constructing a correspond supply chain to ensure each operation process could support the quality goal and maximize the efficiency of utilizing firm’s resources. These are the essential issues that all e-companies need to concern. By employing a qualitative research method, this dissertation studies on the key issues about e-commerce companies offering service/product quality guarantee and managing quality processes in supply chain system, both adoptable management psychology and methodologies are introduced. In addition, the challenges and potential problems within the processes of offering and managing for quality guarantee are identified in order to help e-firms examine their internal and external business environment. Furthermore, corresponding suggestions are listed for firms to overcome the problems and improve business performance management. This study will give readers especially those who are the e-commerce practitioners the systematic understanding of e-commerce management processes. This could help readers in planning for the success in their businesses.